Melakar Masa Depan / Sarman Mohamad - Mohamad, Sarman (Faculty of Art and Design, 2021)
The face of hope captures the essence of unauthorized immigrant children in this country, living without obtaining a good education, an inaccessible living space with an uncertain future, inviting danger, threats and facing socioeconomic disadvantages. A piece of digital in collage on the background as a symbol of the child's soul, two faces and a map as a reflection of the child's life